KONTEN DAN KONSTRUK ASESMEN KETERAMPILAN BERPIKIR EVALUATIF PADA TEMA KARBOHIDRAT DALAM KIMIA PANGAN - Sofia Sofia; Anna Permanasari; Hayat Sholihin; Florentina M T Supriyanti (Orbital: Jurnal Pendidikan Kimia, 2020)
This study aims to obtain an assessment that can be used to measure evaluative thinking skills on the theme of carbohydrates in food chemistry. This study uses a development model that consists of several stages, namely determining learning outcomes, establishing indicators of evaluative thinking, compiling items and assessment guidelines, conducting expert validation, and testing items on students. The test results obtained are scored according to the assessment guidelines. Expert validation was analyzed using Content Validity Ratio (CVR) to determine validity. Analysis of the test items using AnatesV4 to determine the reliability, and the level of difficulty of the questions. The results of the analysis of learning outcomes, carbohydrate material and literacy obtained 10 learning indicators and three indicators of evaluative thinking skills and 4 item description items. The CVR calculation result is 0.84 indicating that the instrument content is valid and can be used for data collection. The results of the trial of the instrument showed that all items were stated to be reliable with a value of 0.85, a very high category and the level of difficulty varied namely easy, medium and difficult. Based on the results of this study it can be concluded the items for evaluative thinking skills assessment on the theme of carbohydrates in food chemistry can be used because it has fulfilled the elements of the validity and reliability of the test.